VEHICLE DETECTION USING PRINCIPAL COMPONENT ANALYSIS - Rifki Kosasih; Achmad Fahrurozi; Iffatul Mardhiyah (Jurnal Ilmiah KOMPUTASI, 2020)
The detection of a vehicle in video is a activity that is important to help the security forces keep an eye on the traffic flow. However, it is hard to security forces to keep watching the video (CCTV) of traffic flow in all day long. Artificial intelligence can be use to help the security to monitoring and analyze the traffic of vehicles, such as to know the level of vehicle traffic density at a certain time period or find out detailed information about the vehicle that want to observe. In this study, Principle Component Analysis (PCA) method used to doing background substraction process to detect vehicles in a real time. To improve the results of PCA method, morphological operation is implemented. The experiment result shown that PCA method is well used to detect the vehicle in a real time with accuracy at 95%.